Male-Female Wage Differentials and the Impact of Equal Pay Legislation - Gunderson, Morley (The Review of Economics and Statistics, 1975)
EMPIRICAL studies tend to confirm the existence of a male-female wage differential based on sex. However, the proportion of the differential attributable to discrimination differs widely, reflecting the problems of adjusting for differences in experience, education, training, absenteeism, and turnover as well as differences in the occupational distribution of females. In the U. S., studies by Fuchs (1971), Cohen (1971) and Oaxaca (1973) imply a proportionate, unadjusted male-female wage differential (Win Wf)/Wf, of about 50%o-80%. Differences in such factors as experience, education, training, absenteeism and turnover account for about half of the gross wage differential. Most of the remaining half is attributed to females being employed in low-wage occupations, a factor not controlled for in their analyses. Sanborn (1964) does adjust for the occupational distribution of females and estimates a differential of approximately 15% within an occupation. Studies by McNulty (1967) and Buckley (1971) also indicate male wages to exceed female wages by about 20%o within select, narrowly-defined occupations (but not within the same establishment). They attribute about half of this differential to females being concentrated in low-wage establishments.